1994
DOI: 10.1063/1.112878
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of optical gain on crystal orientation in surface-emitting lasers with strained quantum wells

Abstract: We analyze theoretically optical gains in vertical-cavity surface-emitting lasers (VCSELs) for various crystal orientations. The calculation based on the multiband effective-mass theory takes into account the effects of anisotropy and nonparabolicity on the valence subband dispersion. It is found that in VCSELs employing InGaAs/InP strained quantum wells (QWs) with non-(001) orientations except (111), the polarization in the QW plane can be controlled and high gains are obtained. In particular, the gains in VC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…Previous approaches include techniques such as fabricating in asymmetric shape 4 -6 and providing asymmetric mechanical force. [7][8][9] Also, it has been shown theoretically 10,11 and experimentally 12,13 that strained multiquantum wells ͑MQWs͒ grown on an asymmetric crystal plane have an asymmetric in-plane gain, which leads to a fixed in-plane polarization axis. These polarization control schemes have been mainly studied on short-wavelength VCSELs, but relatively little has been done on long-wavelength VCSELs.…”
Section: Wavelength Vertical Cavity Surface Emitting Laser Fabricatmentioning
confidence: 99%
“…Previous approaches include techniques such as fabricating in asymmetric shape 4 -6 and providing asymmetric mechanical force. [7][8][9] Also, it has been shown theoretically 10,11 and experimentally 12,13 that strained multiquantum wells ͑MQWs͒ grown on an asymmetric crystal plane have an asymmetric in-plane gain, which leads to a fixed in-plane polarization axis. These polarization control schemes have been mainly studied on short-wavelength VCSELs, but relatively little has been done on long-wavelength VCSELs.…”
Section: Wavelength Vertical Cavity Surface Emitting Laser Fabricatmentioning
confidence: 99%
“…Few results on orientation-dependent growth of InGaAs/InP QW are found in literature [8,9]. Ohtoshi et al reported the dependence of optical gain on crystal orientation in InGaAs/InP surface emitting laser [6]. In 2012, M.M.…”
Section: Introductionmentioning
confidence: 99%
“…If the optical gain in the active region is enhanced, the output-mirror reflectance can be reduced with increase in output power [6]. In recent years, it is unleashed that improved optical gain and threshold current of the lasers can be attained by introducing non-(100)-oriented quantum well (QW) into the active region as the separation between heavy hole (HH) and light hole (LH) is orientation-dependent; so the density of states and speed of carrier transition from valence band (VB) maxima to conduction band (CB) minima at Γ-point.…”
Section: Introductionmentioning
confidence: 99%
“…The problems with random polarization of single mode VCSELs were solved by applying azimuth polarization control techniques. These are usually based on semiconductor substrates with (311) crystallographic orientation in the Miller notation [1][2][3], elliptical shapes of the VCSEL mesa structure [4][5], external mechanical stresses [6] and surface etching technology of diffraction gratings [7]. Up till now, polarization effects in VCSELs are not fully understood and attract a lot of attention in the laser community [8][9][10].…”
mentioning
confidence: 99%
“…Hence, the polarizer is an angle discriminator of the linear polarization in the optical power function. To obtain the best linearity and sensitivity of measurements, the main polarizer axis must be shifted by =45º relative to the linear polarization axis of the laser (1) where: A -initial intensity,  -angle between light polarization direction and axis of polarizer. The value of the measured angle  is burdened with complex measurement uncertainty  ± U  , where we should include the assessment of uncertainty input quantities P opt and A.…”
mentioning
confidence: 99%